The Effect of Work Stress Motivation and Organizational Culture on Employee Performance Through Job Satisfaction as an Intervening Variable: Pengaruh Stres Kerja Motivasi dan Budaya Organisasi terhadap Kinerja Karyawan Melalui Kepuasan Kerja sebagai Variabel Intervening - Satriyo Wibowo, Nur Bahtiar; Sumartik (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to determine the effect of work stress (X1), motivation (X2), and organizational culture (X3) on employee performance (Y) through job satisfaction as an intervening variable (Z). This research has a causal concept with the aim of obtaining truth results whether proven or not. The analytical tool used in this research is path analysis technique with the help of SPSS (Statistical Package for the social science) version 25 for windows. The primary data in this study were obtained from a questionnaire whose measurement was using a Likert scale which was tested using validity and reliability tests. The results of this study show that (1) job stress has a positive and significant effect on job satisfaction, (2) motivation has a positive and significant effect on job satisfaction, (3) organizational culture has a positive and significant effect on job satisfaction, (4) work stress has a positive and significant effect on job satisfaction. positive and significant effect on employee performance, (5) motivation has a positive and significant effect on employee performance, (6) organizational culture has a positive and significant effect on employee performance, (7) job satisfaction has a positive and significant effect on employee performance, (8) work stress positive and significant effect on employee performance through job satisfaction as an intervening variable, (9) motivation has a positive and significant effect on employee performance through job satisfaction as an intervening variable, (10) organizational culture has a positive and significant effect on employee performance through job satisfaction as an intervening variable.